Galectin-9 potentiates salivary gland damage by inducing ferroptosis in Sjogren’s disease - Fangyu Liu; Tiantian Deng; Yan Zhang; Xuanyi Zhou; Zihan Liu; Haojia Zhao; Jiahui Tang; Jing Luo; Qingwen Tao; Zihan Wang (Journal of Molecular Medicine, 2026)

Effects of single and double deletion of Vibrio anguillarum histone-like protein HU subunits on biofilm formation and pathogenicity in flounder (Paralichthys olivaceus) - Jiahui Zhang; Qiwei Sun; Wenting Wang; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Wenbin Zhan; Zhihai Sui; Heng Chi (Fish & Shellfish Immunology, 2026)

Colorful microwave absorbers: Maya-inspired hybrid pigment with flaky carbonyl iron for enhanced absorption performance - Dandan Min; Meng Zhou; Guang Hu; Xiaoyan Gao; Yu Wang; Meiyan Chen; Xinyue Yang; Jiahui Zhi; Yaxin Zheng; Mengling Tang; Chenxi Li (Applied Clay Science, 2026)

How the built environment promotes sustainable commuting mode choice among groups with heterogeneous travel preferences? - Jiahui Zhu; Jia Tang; Siqi Gao; Jun Gao (Sustainable Cities and Society, 2026)

A dual surrogate simulated feedback framework for data-driven coagulant dosage optimization in drinking water treatment - Shuai Yang; Bernard Lassimo Diawara; Qingshi Tu; Huanliang Liu; Jiahui Zhen; Yulin Tang (Journal of Environmental Chemical Engineering, 2026)

Structural characterization of novel polysaccharides from Sargassum fusiforme with dual anticoagulant activity targeting thrombin and antithrombin III - Yue Zhu; Yuanlin Luo; Yunqin Shi; Jiahui Shao; Shunhao Lin; Xiuting Zhang; Yu Tang; Xiangwei Zhao; Jianping Jiang; Zhenzhong Yang (Food Chemistry, 2026)

A cell surface-targeted MNAzyme-aptamer system for highly sensitive and visual detection of cancer cells via nucleolin activation - Yingjie Chen; Lu Tang; Kai Feng; Jiahui Xiang; Yao Liu; Tao Wan; Dairong Li (Analytica Chimica Acta, 2026)

Oxylipins in food and biological systems: from biosynthesis, distribution, and bioactivity to applications in food quality and safety - Shitong Wang; Weibo Lu; Lijun Ge; Huixiang Wu; Jiahui Wu; Keyun Cheng; Hailong Xiao; Xinyuan Wang; Funing Huang; Shiqi Wang; Kang Chen; Yunkai Wu; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Ambient PM2.5 exposure and sleep quality: Evidence from circadian DNA methylation signatures in a population-based study - Yuting Wang; Shuzhen Liu; Jiahui Rong; Yaxin Luo; Siyuan Niu; Peifeng Guo; Xu Tang; Yujian Liang; Xiaoting Mo; Linhai Zhao; Shiwen Jiang; Tiantian Gu; et al. (Journal of Hazardous Materials, 2026)

Phenolic mediated browning of sushi ginger slices during storage and its inhibition by enzyme inactivation and reduced phenolic availability during mild blanching - Jingyang Yu; Jiahui Zhou; Tong Zhou; Yishun Yao; Shuqin Xia; Heping Cui; Jianzeng Liu; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Bioscience, 2026)

Mechanisms and Applications of Coagulation/Flocculation in Oily Wastewater Treatment: A Review of Recent Trends and Perspectives - Shixin Zhang; Yuxin Chen; Xiaomin Tang; Jiahui Zhang; Yixin Zhang; Fengyu Wang; Yu Zhou; Pengcheng Peng; Huaili Zheng (Water, Air, & Soil Pollution, 2026)

The cortical morphology of cingulate cortex and microarchitecture of cingulum bundle correlate with cancer pain and anxiety in lung cancer patients - Lin Tang; Xiaosong Lan; Xiaoyu Zhou; Yu Tang; Jiahui Zheng; Junhao Huang; Yong Tan; Jing Zhang; Hong Yu; Meng Lin; Hua Lan; Xinying Ren; et al. (Brain Imaging and Behavior, 2026)

Cooperative detoxification through GSTm1 and GSTs2 reveals distinct transcription factors BH1 and zen2 in dinotefuran resistance in Nilaparvata lugens - Bingjie Tang; Yutao Hu; Bin Liu; Xin Lei; Pingping Guo; Jiahui Liu; Wenqing Zhang (Pesticide Biochemistry and Physiology, 2026)

Intraperitoneal extracellular trap-derived proteins mediate the amplification of vaccine-induced immune responses in flounder (Paralichthys olivaceus) - Jiahui Zhang; Qian Li; Xiaoqian Tang; Chengxu Ha; Jing Xing; Xiuzhen Sheng; Wenbin Zhan; Heng Chi (Fish & Shellfish Immunology, 2026)

From active defense to cross-kingdom alarm: Rhizosphere microenvironment remodeling in soybean under polylactic acid nanoplastics and cadmium Co-stress - Yuyang Wu; Wenlu Ma; Yue Sun; Jiahui Tang; Xinyu Xu; Jun Zhu; Jinqi Miao; Mingwei Li; Jinpeng Zeng; Kexuan Gou; Yang Song; Jinhua Zou (Journal of Hazardous Materials, 2026)

Physicochemical properties, flavor profile, and alleviation of DSS-induced colitis in mice of co-fermented oat beverage - Jiahui Du; Xinyao Wang; Ganqi Yang; Taizheng Tang; Jiushi Guo; Jin Li; Yifeng Wu; Tungalag Dong; Xueyan Yun (Food Research International, 2026)

Convergent heavy metal profiles shape divergent bacterial community patterns in subtropical water-sediment system - Wenyuan Hu; Wei Ouyang; Shangwei Zhang; Xin Hao; He Zhang; Jiahui Xie; Tianyi An; Shaoqing Liu; Jie Tang (Journal of Hazardous Materials, 2026)

Transgenerational neurotoxicity of plasticizers diisooctyl phthalate (DIOP) in Caenorhabditis elegans - Siyuan Luo; Jiahui Lu; Jiayi Tang; Chenhao Shi; Hang Fai Kwok; Huajun Zhao; Haixin Qin (Chemico-Biological Interactions, 2026)

Hypoxia risk in fragmented streams: cross-scale responses of juvenile Acrossocheilus fasciatus to acute hypoxia–reoxygenation - Yongyao Guo; Wenjie Tang; Jiahui Fang; Qin Xu; Siqiu Chen; Xiaojun Wang; Shanshan Zhao; Bo Zhao (Environmental Biology of Fishes, 2026)

Active chloride-mediated PET microplastic depolymerization via ferroelectric electrocatalysis: Unveiling the dark reaction boosting mechanism - Wei Liu; Yanfei Liu; Xiaochuan Tang; Yanan Jiang; Jiahui Yao; Feipeng Li; Zhiyong Liu; Hong Tao; Shifei Kang (Chemical Engineering Journal, 2026)

Metabolic engineering of dammarane-type ginsenoside biosynthesis in rice endosperm and evaluation the anticancer efficacy of ginsenoside-biofortified rice in vitro and in vivo - Kai You; Cuiyuan Jing; Jiahui Wen; Lin Tang; Bowen Huang; Dongdong Zeng (Chemical Engineering Journal, 2026)

X-ray CT-based investigation of mesoscopic pore structure and macro-meso coupled damage model for anisotropic lean clay under a freeze–thaw cycle - Yu Tang; Ping Yang; Jiahui Wang; Chang Huo (Transportation Geotechnics, 2026)

A high-dielectric additive for enhanced supercapacitor performance with N-doped carbon electrodes - Hongyu Liang; Hui Li; Shengda Tang; Jiahui Li; Zhaomin Zhu; Li Pan; Yongfeng Bu (Chemical Engineering Journal, 2026)

Cropland evapotranspiration based on Sentinel-2 shortwave infrared data and ensemble Kalman filter - Lu Liu; Yunjun Yao; Qingxin Tang; Xueyi Zhang; Yufu Li; Joshua B. Fisher; Jiquan Chen; Jia Xu; Xiaotong Zhang; Ruiyang Yu; Zijing Xie; Jing Ning; et al. (Agricultural and Forest Meteorology, 2026)

Comprehensive single-cell profiling uncovers TsMHC-II expression predicting response to neoadjuvant immunotherapy in gastric cancer - Zhiyuan Xu; Zhichun Tang; Simeng Hu; Litao Yang; Jingli Xu; Pengfei Yu; Yian Du; Yanqiang Zhang; Jiahui Chen; Xiaoxiao Wu; Siwei Pan; ShengJie Zhang; et al. (Science Bulletin, 2026)

A comprehensive and critical review on the removal of pharmaceutical contaminants by coagulation/flocculation: mechanisms, applications and prospects - Shixin Zhang; Yixin Zhang; Jiahui Zhang; Xiaomin Tang; Huaili Zheng; Yu Qin (Journal of Water Process Engineering, 2026)

Short-term black carbon exposure impairs mental health and DNA methylation signatures of mitochondrial carrier genes - Shuzhen Liu; Yaxin Luo; Jiansheng Cai; Yuting Wang; Jiahui Rong; Xiaoting Mo; Yujian Liang; Zeyan Ye; Xu Tang; Siyuan Niu; Tiantian Zhang; Lei Luo; et al. (Journal of Hazardous Materials, 2026)

Multifunctional hydrogel with rigid–flexible synergy enables high-performance flexible supercapacitors and triboelectric nanogenerators - Jiahui Tang; Xi Yang; Jiaojiao Li; Yulin Zou; Cong Chang; Dandan Gao; Jiyang Xie; Qian Zhao; Xu Zhang; Yongyun Mao (Chemical Engineering Journal, 2026)

Masking effects from seasonal rainfall reshape the thresholds of landscape components on water quality in subtropical basins - Jiahui Xie; Cen Meng; Wei Ouyang; Huanyao Liu; Kaiyue Ji; Shaoqing Liu; Jie Tang; Wenyan Tang (Journal of Environmental Management, 2026)

Endocrine disruptive effects and mechanisms of isothiazolinone analogs in marine medaka (Oryzias melastigma) embryos and H295R cells - Jiali Li; Lizhu Tang; Jing Li; Chenyan Hu; Jiahui Cao; Wenbing Zhang; Lianguo Chen (Aquatic Toxicology, 2026)

The Role of Toll-like Receptor 3 Signaling in Cognitive Impairment Induced by Propofol Addiction - Jiahui Wu; Liyun Deng; Rui Gao; Ying Cui; Yidan Tang; Changliang Liu; Tao Zhu; Chan Chen (Molecular Neurobiology, 2026)

Exploring the Role of B-Cell Biotherapy in Myasthenia Gravis from a Genetic Perspective: A Mendelian Randomization Study - Mengyuan Zhang; Cen Yue; Jie Fang; Jiahui Tang; Caihong Chen; Caili Zhou; Wanli Yang; Xingkai An; Qing Lin; Jiawei Zhang (Molecular Neurobiology, 2026)

Mechanism of rock breaking by high voltage electric pulse liquid plasma shockwave breaking - Weiji Liu; Jiahui Zhang; Wuji Tang; Xiaohua Zhu; Siqi Liu; Xin Zhou (Journal of Applied Geophysics, 2025)

Exploration of the multi-dimensional quality deterioration patterns and mechanism analysis of sea urchin gonads during storage at ambient temperature - Jiahui Song; Qiang Geng; Yue Tang; Dong Chen; Songyi Lin (Food Chemistry, 2025)

Multi-modification of food protein: Design, structural transformation, and functional application - Wei Tang; Juan Qu; Yixuan Zhang; Jiahui Chen; Weilin Liu; Jianfei He; Jianhua Liu (Food Chemistry, 2025)

Self-healing, highly stretchable, recyclable PU-curcumin elastomer with substrate-sensitive solid-state fluorescence - Linjie Wei; Xiubin Xu; Hongchun Mu; Wantong Lin; Jiahui Tang; Jieran Li; Jianwei Liu; Haitao Dong; Danfeng Yu; Xu Wu (Chemical Engineering Journal, 2025)

Investigation on the strength characteristics of frozen lean clay influenced by anisotropy - Yu Tang; Jiahui Wang; Ping Yang (Cold Regions Science and Technology, 2025)

Unraveling the potential mechanism and prognostic value of pentose phosphate pathway in hepatocellular carcinoma: a comprehensive analysis integrating bulk transcriptomics and single-cell sequencing data - Bin Li; Tao Zeng; Cui Chen; Yuankai Wu; Shuying Huang; Jing Deng; Jiahui Pang; Xiang Cai; Yuxi Lin; Yina Sun; Yutian Chong; Xinhua Li; et al. (Functional & Integrative Genomics, 2025)

Seasonal rainfall variation disrupted the balance of carbon and nitrogen coupling loss in subtropical acidified watershed - Xin Hao; Jiahui Xie; Wei Ouyang; Jie Tang; Wenyan Tang; He Zhang (Agricultural and Forest Meteorology, 2025)

Turning on and off metal-organic frameworks for the formation of novel core-shell heterojunction catalysts and the controlled piezocatalysis - Miao Huang; Wencong Li; You Li; Jiahui Tang; Xiangdong Xu (Chemical Engineering Journal, 2025)

Establishment of Agrobacterium-mediated genetic transformation in Salix brachista - Dan Tang; Yumeng Li; García-Caparrós Pedro; Jiahui Chen; Xudong Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Ferrous amendment alters rice uptake of tetracyclines and bacterial community compositions in paddy soils - Qingyuan Zhang; Ximan Feng; Hebin Liang; Guiyuan Cai; Jiahui Hu; Zhengxin Xie; Jun Tang (Journal of Hazardous Materials, 2025)

Synergistic dewatering of construction foundation sludge via tripartite strategy: High-efficiency flocculation and floc skeleton reinforcement mechanism - Shixin Zhang; Jiahui Zhang; Dilin He; Yixin Zhang; Shiyu Yuan; Xiaomin Tang; Huaili Zheng; Sen Li; Yuxin Chen; Yu Qin (Journal of Environmental Chemical Engineering, 2025)

Optimization of sandy mudstone substrate for plant growth and soil quality - Huiyuan Zhang; Qi Li; Yuhang Li; Binghe Wang; Yuxin Xiu; Jiahui Zhang; Mengyang Han; Jiahao Tang; Xiangjun Pei (Journal of Environmental Chemical Engineering, 2025)

The antibacterial activity and metabolomic analysis of the recombinant lectin protein PFL-96 derived from Pinctada fucata against Streptococcus agalactiae isolated from tilapia (Oreochromis niloticus) - Xiaojian Mo; Wenyue Li; Jianbing Liu; Qiting Li; Zhongxiu Liang; Xinyu Liang; Jiaxing Tang; Jiahui Liang; Jiang Lin; Peng Liu (Fish & Shellfish Immunology, 2025)

Association and predictive values of nine biological age measures for cardiovascular disease mortality: screening and validation from two prospective cohort studies - Solim Essomandan Clémence Bafei; Hankun Xie; Song Yang; Junxiang Sun; Yu Liu; Yao Fan; Wei Tang; Jiahui Liu; Changying Chen; Chong Shen (GeroScience, 2025)

Characterization of endophytic bacterial communities in Abelmoschus manihot under Cd stress and isolation of Cd-resistant bacteria - Mengxi Wu; Tingting Tang; Qilin Liu; Peng Xiao; Yibo Xiong; Jiahui Feng; Minrui Peng; Jungang Zhu; Xue Yong; Yin Jia; Beibei Jiang; Yezhang Ding; et al. (Journal of Hazardous Materials, 2025)

Hybrid electrospun fibers with metal-based catalysts for zinc-air battery: Recent development and future perspectives - Mahmood ul Haq; Yongbiao Mu; Saz Muhammad; Baoxin Wu; Kejun Yan; Jiahui Luo; Zheng Li; Zhiqing Tang; Muhammad Ajmal; Wenjia Li; Lin Zeng (Chemical Engineering Journal, 2025)

Advances in research on the impact of urban blue-green landscape patterns on heat island effects: a systematic literature review - Yuxiang Lan; Zhanhua Liu; Jiahui Zheng; Yuanyang Tang (Environmental Monitoring and Assessment, 2025)

Fast-selective electro-driven membrane reactor in fluoride/silica crystallization for microelectronic wastewaters recycling - Yangbo Qiu; Lei Xia; Long-Fei Ren; Chao Wang; Yiping Wan; Yan Zhao; Raf Dewil; Bart Van der Bruggen; Jiahui Shao; Chuyang Y. Tang (Water Research, 2025)

Supergravity separation: An innovative strategy for efficient cleaning and upgrading of coal gasification slag waste - Hailong Tang; Jingfeng He; Lixiang Fu; Jiahui Zhang; Liangyu Yao; Bin Yang; Lingtao Zhu; Shihai Guo (Waste Management, 2025)

Nitrogen level determines arbuscular mycorrhizal fungi nitrogen uptake rate of Stipa purpurea in alpine steppe - Jiahui Sun; Yu Tang; Keyu Chen; Shijie Ren; Hailan Shi; Qiang Dong; Junfu Dong; Lin Zhang; Xiaoyong Cui; Yanfen Wang; Baoming Ji; Jing Zhang (Plant and Soil, 2025)

Unlocking the future potential of SWATH-MS: Advancing non-target screening workflow for the qualitative and quantitative analysis of emerging contaminants - Di Xia; Guofang Pan; Yaxiong Liu; He Liu; Bo Zhao; Jiahui Wu; Ting Tang; Guining Lu; Rui Wang (Water Research, 2025)

Polydatin mitigates seizures via mitochondrial protection: Mechanisms unraveled by network pharmacology and experimental validation - Yahong Cheng; Yi Ding; Ziyan Tang; Xiaoyi Lei; Yufang Ma; Mengxin Xia; Jiaying Li; Gaoge Hu; Jiahui Zhang; Jing Rao (Food Bioscience, 2025)

Coupling Spectral Indices and Machine Learning to Compare GF-6 and Sentinel-2A Data in Forest Health Monitoring - Jiahui Chen; Hanqiu Xu; Fei Tang (Chinese Geographical Science, 2025)

Constructing a stable mannitol biosynthetic pathway in cyanobacteria via the introduction of heterologous mannitol dehydrogenase - Jiahui Sun; Xiangyi Yuan; Jinhui Tang; Huili Sun; Guodong Luan; Xuefeng Lu (Algal Research, 2025)

Research on Variable Circulation Design Method and Internal Flow Characteristic of the Axial Flow Pump - Xuewei Yu; Qili Gan; Zifan Ling; Jiahui Gong; Jiajia Tang; Lijian Shi (Journal of Marine Science and Engineering, 2025)
To investigate the influence of circulation distribution on axial-flow pump performance, this study integrates numerical simulation and theoretical analysis methods, establishing a simulation framework based on MATLAB and CFX. By adjusting the circulation distribution function from the hub to the tip of the impeller, various design models were constructed. Three-dimensional parametric modeling of the blades was achieved through MATLAB programming, generating key parameters such as blade profile coordinates. Subsequently, the geometric data were imported into CFX to establish a full-flow passage numerical model. The simulation employed the RANS equations with the k-ε turbulence model to analyze flow field characteristics and hydraulic performance under different circulation schemes. Numerical results indicate that under identical circulation distributions, the head–flow curve exhibits a monotonically decreasing trend, while the efficiency curve demonstrates a distinct single-peak characteristic. Notably, under specific design conditions, variations in design parameters can shift the best efficiency point while simultaneously improving efficiency. Cavitation performance analysis reveals that as the hub-to-tip ratio increases, the velocity circulation initially rises rapidly before gradually stabilizing. This distribution pattern effectively optimizes the pressure gradient at the impeller outlet, thereby significantly enhancing cavitation resistance across a wide operational range. The proposed circulation control methodology provides critical theoretical support and engineering guidance for the hydrodynamic optimization of low-head axial flow pumps.

Discovery of XY Sex Chromosomes in Mauremys mutica Provides Insights Into the Role of KDM6B Gene in Coexistence of Temperature‐Dependent and Genetic Sex Determination - Jianjun Liu; Siqi Liu; Jinxiu Dong; Min Tang; Taiyue Li; Jiahui Li; Xinjiang Bu; Xingquan Xia; Huaxing Zhou; Liuwang Nie (Molecular Ecology, 2025)
The Asian yellow pond turtle ( Mauremys mutica ) has long been thought to lack dimorphic sex chromosomes, with prevailing theories suggesting a solely temperature‐dependent sex determination (TSD) system. In this study, a male chromosome‐level genomic sequence with a contig N50 of ~23.59 Mb was generated using a combination of both Nanopore and Hi‐C sequencing technologies. We utilise a combination of bioinformatics and cytogenetic experimental validation to demonstrate that this species indeed possesses XY chromosomes, thereby correcting a longstanding misconception. The results suggest that the X chromosome of the Asian yellow pond turtle originated independently during later stages of evolution and underwent chromosomal rearrangements. Notably, it was observed that the sex chromosomes exhibited a significant repeat expansion, with 95.9% comprising repetitive sequences. This expansion is primarily driven by LINE/CR1 repeats, which account for 55.2% of the total length of the X chromosome. We found that the X chromosome underwent a lower rate of adaptive evolution, supporting the concept of the “slower‐X” effect. We present a novel model concerning the KDM6B , which is located on both XY chromosomes, mediates a sex determination mechanism that coexists with TSD + XY in turtles. This study paves the way for further exploration into the complexities of sex determination and the evolutionary dynamics of sex chromosomes in turtles and potentially other reptiles.

White matter integrity mediated the effect of plasma uric acid levels on cognitive function in ALS patients - Jiahui Tang; Yali Zhao; Yu Chen; Yuan Yang; Zhenxiang Gong; Zehui Li; Min Zhang; Jing Zhang (Brain Imaging and Behavior, 2025)

miR-9a and miR-10482-5p regulate the expression of chitin synthase and chitinase genes, enhancing lufenuron tolerance in Spodoptera frugiperda - Shanshan Ling; Zhimin Guo; Mengyan Wu; Jiahui Tang; Haixiang Lv; Jianhong Li; Kangsheng Ma (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Wet and dry deposition of atmospheric nitrogen to Lake Erhai basin: Composition, spatiotemporal patterns and implications for nitrogen inputs into the lake - Jiahui Kang; Xiaoyun Du; Bowen Tang; Qikun Shen; Jiawei Li; Yuepeng Pan; Mathew R. Heal; Xuejun Liu; Wen Xu (Atmospheric Environment, 2025)

Impact of snow on vegetation green-up dynamics on the Tibetan Plateau: Integration of survival analysis and remote sensing data - Jingyi Xu; Yao Tang; Jiahui Xu; Jin Chen; Song Shu; Jingwen Ni; Xiaoqi Zhou; Bailang Yu; Jianping Wu; Yan Huang (Agricultural and Forest Meteorology, 2025)

Potentially harmful effects of micro-/nanoplastics on humans as well as protective actions of dietary natural products - Jin Cheng; Jiahui Li; Ruo-Gu Xiong; Dan-Dan Zhou; Si-Yu Huang; Si-Xia Wu; Ao Shang; Guo-Yi Tang; Hua-Bin Li; Ren-You Gan (Trends in Food Science & Technology, 2025)

Graphene oxide supported-stabilized oxygen defective CoCr2O4 for boosted bifunctional electrocatalytic oxygen evolution and urea oxidation - Jiahui Liao; Changcun Tang; Yiting Sun; Xilin Wang; Yanhe Xiao; Baochang Cheng; Shuijin Lei (Fuel, 2025)

Weak interaction strategy enables enhanced selectivity and reusability of arginine-functionalized imprinted aerogel for phosphate adsorption - Lidong Feng; Tianxiao Leng; Yangbo Qiu; Chao Wang; Long-Fei Ren; Haoyu Sun; Liang Tang; Jiahui Shao; Minghong Wu (Bioresource Technology, 2025)

A self-designed pyrolysis-gasification-combustion pilot plant for rural solid waste disposal: The elucidation of emission factors - Wei Jiang; Dian Li; Hui Cai; Jiahui Yan; Yuanyao Ye; Jianxiong Kang; Qian Tang; Yongzheng Ren; Songlin Wang; Dongqi Liu; Zizheng Liu; Yiqun Chen (Atmospheric Pollution Research, 2025)

Deep Brain Stimulation Inhibits Epileptic Seizures via Increase of Adenosine Release and Inhibition of ENT1, CD39, and CD73 Expression - Zhonghua Xiong; Jiahui Deng; Pandeng Xie; Chongyang Tang; Jing Wang; Qinqin Deng; Yujiao Yang; Jing Zhang; Mengyi Guo; Xiongfei Wang; Yuguang Guan; Guoming Luan; et al. (Molecular Neurobiology, 2025)

Microbial flocculants for removing multiple pollutants in wastewater: A review of recent trends and perspectives - Sen Li; Jiahui Zhang; Yan Liu; Nanchuan Song; Wenli Li; Longqing Tang; Huaili Zheng; Yixin Zhang; Yuxin Chen; Shixin Zhang (Journal of Water Process Engineering, 2025)

Multifunctional nanofiber system with photothermal-controlled drug delivery and motion monitoring capabilities as intelligent wound dressing - Peiran Lin; Kaitong He; Jiahui Luo; Jiyuan Wang; Yuting Liu; Jian Zhang; Hao Fan; Shunfen Huang; Wei Lan; Wenlong Wang; Xuhui Zhang; Botao Gao; et al. (Chemical Engineering Journal, 2025)

Effects of Microplastics Exposure on the Feeding of the Heterotrophic Dinoflagellate Species Noctiluca scintillans - Chi Hung Tang; Jiahui Chen (Water, Air, & Soil Pollution, 2024)

MicroRNA-451 Regulates Angiogenesis in Intracerebral Hemorrhage by Targeting Macrophage Migration Inhibitory Factor - Shuang Bai; Ge Zhang; Shiling Chen; Xuan Wu; Jiarui Li; Jingxuan Wang; Danyang Chen; Xia Liu; Jiahui Wang; Yuanwei Li; Yingxin Tang; Zhouping Tang (Molecular Neurobiology, 2024)
Intracerebral hemorrhage (ICH) is a subtype of stroke with the highest fatality and disability rate. Up to now, commonly used first-line therapies have limited value in improving prognosis. Angiogenesis is essential to neurological recovery after ICH. Recent studies have shown that microRNA-451(miR-451) plays an important role in angiogenesis by regulating the function of vascular endothelial cells. We found miR-451 was significantly decreased in the peripheral blood of ICH patients in the acute stage. Based on the clinical findings, we conducted this study to investigate the potential regulatory effect of miR-451 on angiogenesis after ICH. The expression of miR-451 in ICH mouse model and in a hemin toxicity model of human brain microvascular endothelial cells (hBMECs) was decreased the same as in ICH patients. MiR-451 negatively regulated the proliferation, migration, and tube formation of hBMECs in vitro . MiR-451 negatively regulated the microvessel density in the perihematoma tissue and affected neural functional recovery of ICH mouse model. Knockdown of miR-451 could recovered tight junction and protect the integrity of blood-brain barrier after ICH. Based on bioinformatic programs, macrophage migration inhibitory factor (MIF) was predicted to be the target gene and identified to be regulated by miR-451 inhibiting the protein translation. And p-AKT and p-ERK were verified to be downstream of MIF in angiogenesis. These results all suggest that miR-451 will be a potential target for regulating angiogenesis in ICH.

Organic carbon inputs shift the profiles of phosphorus cycling-related genes in maize rhizosphere - Yanlan Huang; Jiahui Lin; Caixian Tang; Jianming Xu (Plant and Soil, 2024)

The effect of dietary changes on the water and carbon footprints in China - Jiahui Wang; Yali Yin; Shikun Sun; Jinfeng Zhao; Yihe Tang; Yubao Wang; Pute Wu (Sustainable Production and Consumption, 2024)

Assessing local economic impact of urban energy transition through optimized resource allocation in renewable energy - Jiahui Tang; Wangwang Ding (Sustainable Cities and Society, 2024)

High-resolution and real-time wastewater viral surveillance by Nanopore sequencing - Xiaoqing Xu; Yu Deng; Jiahui Ding; Qinling Tang; Yunqi Lin; Xiawan Zheng; Tong Zhang (Water Research, 2024)

Investigation of lambda-cyhalothrin resistance in Spodoptera frugiperda: Heritability, cross-resistance, and mechanisms - Zhimin Guo; Jiahui Tang; Huina Ma; Mengyan Wu; Shun He; Hu Wan; Kangsheng Ma; Jianhong Li (Pesticide Biochemistry and Physiology, 2024)

Improvement of biotic nitrate reduction in constructed photoautotrophic biofilm-soil microbial fuel cells - Yu Cheng; Jue Ding; Jiahui Wan; Li Tang; Akaninyene Joseph; Muhammad Usman; Ningyuan Zhu; Yanxia Zhang; Han Sun; Eldon R. Rene; Marton Lendvay; Yiping Li (Journal of Environmental Management, 2024)

The triacylglycerol structures are key factors influencing lipid digestion in preterm formulas during in vitro digestion - Jiahui Yu; Huijia Lu; Xinghe Zhang; Juncheng Tang; Zuoliang Liu; Qingzhe Jin; Wei Wei; Xingguo Wang (Food Chemistry, 2024)

A rapid field crop data collection method for complexity cropping patterns using UAV and YOLOv3 - Huifang Zhang; Binyao Wang; Zhonggang Tang; Jiahui Xue; Ruihang Chen; Hongcheng Kan; Shumiao Lu; Lina Feng; Ye He; Shuhua Yi (Frontiers of Earth Science, 2024)

Neural radiance fields for multi-scale constraint-free 3D reconstruction and rendering in orchard scenes - Jing Zhang; Xin Wang; Xindong Ni; Fangru Dong; Longrunmiao Tang; Jiahui Sun; Ye Wang (Computers and Electronics in Agriculture, 2024)

Evaluation of seven satellite-based and two reanalysis global terrestrial evapotranspiration products - Zijing Xie; Yunjun Yao; Qingxin Tang; Meng Liu; Joshua B. Fisher; Jiquan Chen; Xiaotong Zhang; Kun Jia; Yufu Li; Ke Shang; Bo Jiang; Junming Yang; et al. (Journal of Hydrology, 2024)

Sustainable, efficient, and synergistic photocatalytic degradation toward organic dyes and formaldehyde gas via Cu2O NPs@wood - Lingling Wang; Maojie Tang; Haiqiu Jiang; Jiahui Dai; Ruifeng Cheng; Bei Luo; Long Yang; Guanben Du; Wei Gao (Journal of Environmental Management, 2024)

Apatite chemistry of Late Triassic granitic rocks from Yidun Terrane: Implications for petrogenesis and mineralization - Zhuanrong Sun; Guochen Dong; Jiahui Tang; Jianheng Guo; Zhongbao Wang (Mineralogy and Petrology, 2023)

Evaluation of the toxic effects of fluindapyr, a novel SDHI fungicide, to the earthworms Eisenia fetida - Chenyang Ji; Jiahui Miao; Bin Xia; Yaoyao Dai; Jiawen Yang; Guizhen Zhang; Quan Zhang; Feidi Wang; Tao Tang; Meirong Zhao (Science of The Total Environment, 2023)

Correction to: Effects of Dl-3‑n‑butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Effects of Dl-3-n-butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Vascular cognitive impairment (VCI) has been one of the major types of cognitive impairment. Blood–brain barrier damage plays an essential part in the pathogenesis of VCI. At present, the treatment of VCI is mainly focused on prevention, with no drug clinically approved for the treatment of VCI. This study aimed to investigate the effects of DL-3-n-butylphthalide (NBP) on VCI rats. A modified bilateral common carotid artery occlusion (mBCCAO) model was applied to mimic VCI. The feasibility of the mBCCAO model was verified by laser Doppler, 13 N-Ammonia-Positron Emission Computed Tomography (PET), and Morris Water Maze. Subsequently, the Morris water maze experiment, Evans blue staining, and western blot of tight junction protein were performed to evaluate the effect of different doses of NBP (40 mg/kg, 80 mg/kg) on the improvement of cognitive impairment and BBB disruption induced by mBCCAO. Immunofluorescence was employed to examine the changes in pericyte coverage in the mBCCAO model and the effect of NBP on pericyte coverage was preliminarily explored. mBCCAO surgery led to obvious cognitive impairment and the decrease of whole cerebral blood flow, among which the blood flow in the cortex, hippocampus and thalamus brain regions decreased more significantly. High-dose NBP (80 mg/kg) improved long-term cognitive function in mBCCAO rats, alleviated Evans blue leakage and reduced the loss of tight junction proteins (ZO-1, Claudin-5) in the early course of the disease, thereby exerting a protective effect on the blood–brain barrier. No significant changes in pericyte coverage were observed after mBCCAO. High-dose NBP improved cognitive function in mBCCAO rats. High-dose NBP protected the integrity of BBB by upregulating TJ protein expression, rather than regulating pericyte coverage ratio. NBP could be a potential drug for the treatment of VCI.

Efficient extraction and recovery of lithium from waste aluminum cryolite electrolyte - Chaobo Tang; Jiahui Wang; Shenghai Yang; Xianpan Zhang; Shuai Li; Yanqing Lai; Zhongliang Tian; Shengming Jin; Yongming Chen (Resources, Conservation and Recycling, 2023)

Soil moisture at 30 m from multiple satellite datasets fused by random forest - Jing Ning; Yunjun Yao; Qingxin Tang; Yufu Li; Joshua B. Fisher; Xiaotong Zhang; Kun Jia; Jia Xu; Ke Shang; Junming Yang; Ruiyang Yu; Lu Liu; et al. (Journal of Hydrology, 2023)

Carbon-coating small-molecule organic bipolar electrodes for symmetric Li-dual-ion batteries - Chenbin Tang; Bangshuai Wei; Wu Tang; Yan Hong; Meichen Guo; Xuesong He; Jiahui Hu; Shan Jia; Cong Fan (Chemical Engineering Journal, 2023)

Coupling a light use efficiency model with a machine learning-based water constraint for predicting grassland gross primary production - Ruiyang Yu; Yunjun Yao; Qingxin Tang; Changliang Shao; Joshua B. Fisher; Jiquan Chen; Kun Jia; Xiaotong Zhang; Yufu Li; Ke Shang; Junming Yang; Lu Liu; et al. (Agricultural and Forest Meteorology, 2023)

Electrostatically reinforced and sealed nanocellulose-based macrosphere by alginate/chitosan multi-layer coatings for delivery of probiotics - Qian Luan; Hao Zhang; Jiahui Wang; Yan Li; Miaoyu Gan; Qianchun Deng; Luyun Cai; Hu Tang; Fenghong Huang (Food Hydrocolloids, 2023)

New insights into the protection of dietary components on anxiety, depression, and other mental disorders caused by contaminants and food additives - Ruo-Gu Xiong; Jiahui Li; Jin Cheng; Si-Xia Wu; Si-Yu Huang; Dan-Dan Zhou; Adila Saimaiti; Ao Shang; Guo-Yi Tang; Hua-Bin Li; Ren-You Gan; Yibin Feng (Trends in Food Science & Technology, 2023)

Changes in soil Cd contents and microbial communities following Cd-containing straw return - Haojie Xu; Yu Huang; Xinquan Xiong; Hang Zhu; Jiahui Lin; Jiachun Shi; Caixian Tang; Jianming Xu (Environmental Pollution, 2023)

Aberrant adenosine signaling in patients with focal cortical dysplasia - Mengyi Guo; Jing Zhang; Jing Wang; Xiongfei Wang; Qing Gao; Chongyang Tang; Jiahui Deng; Zhonghua Xiong; Xiangru Kong; Yuguang Guan; Jian Zhou; Detlev Boison; et al. (Molecular Neurobiology, 2023)

Preparation and evaluation of a novel alginate-arginine-zinc ion hydrogel film for skin wound healing - Ganzhe Mao; Shuya Tian; Yanxia Shi; Jiahui Yang; Haiying Li; Hongbo Tang; Wenzhi Yang (Carbohydrate Polymers, 2023)

Orally administered BZL-sRNA-20 oligonucleotide targeting TLR4 effectively ameliorates acute lung injury in mice - Dandan Zhao; Yuhao Qin; Jiaqi Liu; Kegong Tang; Shuaiyao Lu; Zirui Liu; Yexuan Lin; Cong Zhang; Fengming Huang; Jiahui Chang; Chang Li; Mingyao Tian; et al. (Science China Life Sciences, 2023)

Phenotype and metabolism alterations in PCB-degrading Rhodococcus biphenylivorans TG9T under acid stress - Aili Li; Jiahui Fan; Yangyang Jia; Xianjin Tang; Jingwen Chen; Chaofeng Shen (Journal of Environmental Sciences, 2023)

Mitigating soil salinity stress with titanium gypsum and biochar composite materials: Improvement effects and mechanism - Xin Xu; Jiahui Wang; Yiming Tang; Xuedan Cui; Daibing Hou; Hongjun Jia; Shaobo Wang; Lin Guo; Jinhang Wang; Aijun Lin (Chemosphere, 2023)

Abatement of binary gaseous chlorinated VOC by biotrickling filter: Performance, interactions, and microbial community - Qian Li; Zeqin Tang; Dujuan Ou Yang; Jiahui Zhang; Jianmeng Chen; Dongzhi Chen (Chemosphere, 2023)

Ionic resource recovery for carbon neutral papermaking wastewater reclamation by a chemical self-sufficiency zero liquid discharge system - Yangbo Qiu; Sifan Wu; Lei Xia; Long-Fei Ren; Jiahui Shao; Jiangnan Shen; Zhe Yang; Chuyang Y. Tang; Chao Wu; Bart Van der Bruggen; Yan Zhao (Water Research, 2023)

Sphingosine 1-phosphate alleviates radiation-induced ferroptosis in ovarian granulosa cells by upregulating glutathione peroxidase 4 - Jiahui Zhao; Mingyan Tang; Huaiyun Tang; Mei Wang; Huijuan Guan; Lisha Tang; Hong Zhang (Reproductive Toxicology, 2023)

Design of bipolar polymer electrodes for symmetric Li-dual-ion batteries - Bangshuai Wei; Yan Hong; Wu Tang; Meichen Guo; Xuesong He; Chenbin Tang; Jiahui Hu; Cong Fan (Chemical Engineering Journal, 2023)

Methylene blue adsorption derived thermal insulating N, S-co-doped TiC/carbon hybrid aerogel for high-efficient absorption-dominant electromagnetic interference shielding - Zhengzheng Guo; Penggang Ren; Jin Wang; Xin Hou; Jiahui Tang; Zongbin Liu; Zhengyan Chen; Yanling Jin; Fang Ren (Chemical Engineering Journal, 2023)

Shift work and nonalcoholic fatty liver disease incidence among Chinese rail workers: a 4-year longitudinal cohort study - Jiahui Xu; Shu Ni; Yuming Wang; Mengfan Yan; Xueli Yang; Han Ge; Zizhuo Jia; Ze Yang; Anqi Shan; Huanyu Liu; Nai-jun Tang (International Archives of Occupational and Environmental Health, 2023)

Association between cold spells and serum lipid levels among the elders: a distributed-lagged effects analysis - Jiahui Lao; Guoyong Ding; Yafei Liu; Fang Tang (Environmental Science and Pollution Research, 2022)

Simultaneous biodegradation of dimethyl sulfide and 1-propanethiol by Pseudomonas putida S-1 and Alcaligenes sp. SY1: “Lag” cause, reduction, and kinetics exploration - Qian Li; Zeqin Tang; Jiahui Zhang; Jingtao Hu; Jianmeng Chen; Dongzhi Chen (Environmental Science and Pollution Research, 2022)

Preoperative Characteristics of Ocular Biometry in Children with Unilateral Congenital Cataracts - Jiahui Chen; Yating Tang; Yongxiang Jiang; Yi Lu (Phenomics, 2022)

Vacuum-Assisted Closure and Skin Grafting Combined with Amphotericin B for Successful Treatment of an Immunocompromised Patient with Cutaneous Mucormycosis Caused by Mucor irregularis: A Case Report and Literature Review - Xuhua Tang; Penghao Guo; Hioteng Wong; Jiahui Xie; Jiande Han; Yingbin Xu; Hui Zhou (Mycopathologia, 2021)

Anti-inflammatory activities of puerarin in high-fat diet-fed rats with streptozotocin-induced gestational diabetes mellitus - Wenting Xu; Mengyu Tang; Jiahui Wang; Lihong Wang (Molecular Biology Reports, 2020)
To investigate the effect of puerarin on insulin resistance and inflammation in rats with gestational diabetes mellitus (GDM). Gestational diabetic model rats were established by intraperitoneal injection of streptozotocin (25 mg/kg) combined with high-fat feeding and were randomly assigned to three groups: the control group, the GDM group, and the puerarin-treated group. Puerarin was intragastrically administered to rats daily until the offspring were born. The rats in both the GDM group and control group were administered the same volume of normal saline. Serum total cholesterol, triglycerides, high-density lipoprotein cholesterol, and low-density lipoprotein cholesterol in all groups of rats were measured. Haematoxylin and eosin staining was used to evaluate morphological changes in the liver, pancreas, and adipose tissues around the reproductive organs. Western blotting was carried out to measure the protein expression of IRS-1 and inflammatory factors, including TNF-α, TLR4, MyD88 and phosphorylated NF-κB, in the adipose tissues around the reproductive organs. Puerarin had preventive effects on GDM-induced pathological changes and ameliorated glucose and lipid metabolism disorders in GDM rats. Puerarin upregulated IRS-1 expression and decreased the protein expression of TNF-α, TLR4, and MyD88 as well as the levels of phosphorylated NF-κB in adipose tissues around the reproductive organs in GDM rats. This study indicated that puerarin exerts anti-inflammatory effects by downregulating the important TLR4/MyD88/NF-κB inflammatory signalling pathway. Therefore, puerarin can decrease the expression of TNF-α and ameliorate insulin resistance in GDM rats, suggesting the potential efficacy of puerarin in GDM treatment.

Animal models of transient ischemic attack: a review - Jiahui Wang; Ping Zhang; Zhouping Tang (Acta Neurologica Belgica, 2020)
Transient ischemic attack (TIA) is defined as a brief episode of neurological dysfunction caused by focal cerebral ischemia. TIA is a critical early warning signal of stroke. Patients with TIA may have long-term cognitive decline. The pathogenesis and pathological changes of TIA have not been fully elucidated. Animal models can simulate the process of human diseases and are essential tools to investigate injury mechanisms and therapeutic approaches of TIA. Most TIA animal models are based on ischemic stroke models and the definition of TIA. Each model has unique strengths and weaknesses. The establishment of a successful and reliable TIA model should follow three criteria: (1) objective evidence of cerebral arteries occlusion and reperfusion, (2) no permanent neurological deficit, and (3) no acute cerebral infarction. However, experimental animal models are impossible to be completely consistent with human TIA, because TIA itself is a heterogeneous disease. In the present review, the selection of animals, methodological development, and evaluation of cerebral blood flow of animal models of TIA are comprehensively evaluated.

Allicin inhibits mouse colorectal tumorigenesis through suppressing the activation of STAT3 signaling pathway - Xiang Li; Jiahui Ni; Yixin Tang; Xu Wang; Huanhuan Tang; Haidong Li; Sulin Zhang; Xiaoyan Shen (Natural Product Research, 2019)

Experimental study of the influence of water content on energy conversion of coal and gas outburst - Lili Li; Jupeng Tang; Shengjie Sun; Jiahui Ding (Natural Hazards, 2019)

Four mononuclear platinum(II) complexes: synthesis, DNA/BSA binding, DNA cleavage and cytotoxicity - Qingming Wang; Lei Yang; Jiahui Wu; Hua Wang; Jialiang Song; Xinhui Tang (BioMetals, 2017)

Association study of common variations of FBN1 gene and essential hypertension in Han Chinese population - Jinfeng Chen; Song Yang; Xianghai Zhao; Jiahui Shen; Hairu Wang; Yanchun Chen; Yanni Ji; Wen Wang; Wei Zhou; Xuecai Wang; Junming Tang; Xiangfeng Lu; et al. (Molecular Biology Reports, 2014)

Preparation and the antitumor activity in vitro of polysaccharides from Tricholoma matsutake - Shuang Yang; Xiaodong Ren; Jingxue Sheng; Jiahui Lu; Tingting Li; Fangrong Tang; Yanfeng Wang; Lingjun Meng; Qingfan Meng; Lirong Teng (World Journal of Microbiology and Biotechnology, 2010)

A PCR-based technology for rapid screening of genomic DNA library - Yongxiang Zhao; Jiahui Zhang; Qi Tang; Zhonggui Shan; Qinming Fan (Bulletin of Experimental Biology and Medicine, 2007)